Ayat-Ayat AlQuran Tentang Manajemen Mutu Pendidikan Islam - Yanti Fatmariyanti; Suhada; Abdul Muin Bahaf; Rijal Firdaos (INDOPEDIA (Jurnal Inovasi Pembelajaran dan Pendidikan), 2023)
Quality management in Islamic education is inseparable from integrated quality management or Total Quality Management (TQM) which is a process and basic philosophy that will be successful if implemented simultaneously at all levels in the organization. Commitment or awareness is needed to carry out cultural changes that are oriented towards improving quality and improving the entire process continuously, comprehensively and continuously. This study aims to find out how the Quality Management of Islamic Education is in the perspective of the verses of the Qur'an. The writing method in this study uses qualitative research methods, by conducting literature searches, searching relevant sources and searching data via the internet, electronic media, and some relevant literature. Quality education will produce intelligent and competitive human resources. Quality national education is contained in Government Regulation Number 9 of 2005 concerning National Education Standards which contains eight national education standards, so that it can be said that Islamic education institutions are quality if they implement eight national education standards